2019
DOI: 10.3349/ymj.2019.60.11.1067
|View full text |Cite|
|
Sign up to set email alerts
|

Bone Flap Changes after Cranioplasty Using Frozen Autologous Bone Flaps: A Three-Dimensional Volumetric Reconstruction Study

Abstract: PurposeBone flap resorption (BFR) after cranioplasty with an autologous bone flap (ABF) is well known. However, the prevalences and degrees of BFR remain unclear. This study aimed to evaluate changes in ABFs following cranioplasty and to investigate factors related with BFR.Materials and MethodsWe retrospectively reviewed 97 patients who underwent cranioplasty with frozen ABF between January 2007 and December 2016. Brain CT images of these patients were reconstructed to form three-dimensional (3D) images, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In a recent study, using 3D image analysis system, different grades of BFR have been observed in 77% of patients. 20 Our overall rate of BFR (26.1%) can be considered as an intermediate level, compared to the limits of the range provided by literature on this subject (2.5% to 50%). In our study, the only significant factor associated with this complication was early cranioplasty, which represented 13/16 cases (81.2%) (table 2).…”
Section: Discussionmentioning
confidence: 70%
“…In a recent study, using 3D image analysis system, different grades of BFR have been observed in 77% of patients. 20 Our overall rate of BFR (26.1%) can be considered as an intermediate level, compared to the limits of the range provided by literature on this subject (2.5% to 50%). In our study, the only significant factor associated with this complication was early cranioplasty, which represented 13/16 cases (81.2%) (table 2).…”
Section: Discussionmentioning
confidence: 70%
“…BFR, which is also called aseptic bone necrosis or osteonecrosis, has been long recognized as the most common ABF-specific cranioplasty complication with an estimated pooled incidence of 15% to almost every second patient, according to recently published clinical systematic reviews [ 3 , 4 , 6 , 8 ]. Further specific volumetric studies on ABFs identified much higher rates of BFR, namely from 77 to 90% [ 9 , 10 ]. Spake et al reported a rate of 82% for clinically relevant BRF depicted on cranial CT among their cohort, whereas BRF progressed over the years in a linear and continuous manner [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…6 However, the problem of bone resorption due to the lack of nutrition must be considered; in almost one-third of cases, this leads to conspicuous contour irregularities and unsatisfactory cosmetic results and, in extreme cases, loss of the implanted bone. 7,8 Cranioplasty with PMMA is similarly cost-effective and can be manufactured to properly cover the bone defect. 3 However, some authors have found that PMMA cranioplasties cause slightly more complications 9 and significantly higher infection rates.…”
mentioning
confidence: 99%
“…The treatment of skull defects with the autologous bone flap is one of the methods employed in everyday neurosurgical practice 6 . However, the problem of bone resorption due to the lack of nutrition must be considered; in almost one-third of cases, this leads to conspicuous contour irregularities and unsatisfactory cosmetic results and, in extreme cases, loss of the implanted bone 7,8 . Cranioplasty with PMMA is similarly cost-effective and can be manufactured to properly cover the bone defect 3 .…”
mentioning
confidence: 99%